2022
DOI: 10.5753/jserd.2021.1931
|View full text |Cite
|
Sign up to set email alerts
|

Tool Proposal for Recommending Design Thinking Techniques in Software Development

Abstract: Design Thinking (DT) has been incorporated into software processes by teams from startups to large companies, used in problem exploration fostering innovative solutions, and integrated into agile methods to satisfy the real stakeholders’ needs. DT places the customer needs up-front and helps to empathize with users, examining their behaviors, and producing outcomes focused on users’ demand. A set of techniques, like personas and user journey, can be used to support this human-centered approach. Selecting which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Parizi et al 53 proposed Helius, a system that helps decision‐making based on the experience and evaluations of professionals regarding the use of DT techniques. The authors evaluated the proposed tool against existing ones and concluded that Helius innovates by considering the professionals' collaborations when feeding the recommendation algorithms.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Parizi et al 53 proposed Helius, a system that helps decision‐making based on the experience and evaluations of professionals regarding the use of DT techniques. The authors evaluated the proposed tool against existing ones and concluded that Helius innovates by considering the professionals' collaborations when feeding the recommendation algorithms.…”
Section: Background and Related Workmentioning
confidence: 99%
“…They must develop solutions to solve the real needs of users and customers, i.e., solutions that customers want (Edison et al, 2015;Pereira et al, 2021). Therefore, user-centered approaches are increasingly being applied in the conception of software products in teams of different sizes (Parizi et al, 2022) because these approaches prioritize the identification of needs and the involvement of real users in the product design process (Carrol & Casselman, 2019) rather than just refining previously defined software requirements (Signoretti et al, 2020). This is important because it is widely recognized that real users should validate business ideas from the very beginning of their conception (Hokkanen & Leppänen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the challenge related to the small number of professionals with knowledge of DT can be justified by the difficulty of implementing the ideas and concepts of the approach and acquiring new skills, considering the large number of available tools for DT (Carlgren et al, 2016). Parizi et al (2022) conducted a systematic mapping of the application of DT in software development, and no studies were identified focusing on establishing alternatives to overcome resistance to using DT.…”
Section: Introductionmentioning
confidence: 99%